COVID-19 and a Tale of Three Drugs: To Repurpose, or Not to Repurpose–That Was the Question - Chris R. Triggle; Ross MacDonald (Viruses, 2025)
On 11 March 2020, the World Health Organisation (WHO) declared a global pandemic caused by the SARS-CoV-2 coronavirus that earlier in February 2020 the WHO had named COVID-19 (coronavirus disease 2019). There were neither drugs nor vaccines that were known to be effective against the virus, stimulating an urgent worldwide search for treatments. An evaluation of existing drugs by ‘repurposing’ was initiated followed by a transition to de novo drug discovery. Repurposing of an already approved drug may accelerate the introduction of that drug into clinical use by circumventing early, including preclinical studies otherwise essential for a de novo drug and reducing development costs. Early in the pandemic three drugs were identified as repurposing candidates for the treatment of COVID-19: (i) hydroxychloroquine, an anti-malarial also used to treat rheumatoid arthritis and lupus; (ii) ivermectin, an antiparasitic approved for both human and veterinary use; (iii) remdesivir, an anti-viral originally developed to treat hepatitis C. The scientific evidence, both for and against the efficacy of these three drugs as treatments for COVID-19, vied with public demand and politicization as unqualified opinions clashed with evidence-based medicine. To quote Hippocrates, “There are in fact two things, science and opinion; the former begets knowledge, the latter ignorance”.